Fentanyl assisted treatment: a possible role in the opioid overdose epidemic? - Geoff Bardwell; Evan Wood; Rupinder Brar (BMC, 2019)
Abstract Background The current opioid overdose epidemic affecting communities across North America is increasingly driven by illicitly manufactured fentanyl and its related analogues. A variety of public health interventions have been implemented and scaled up, including opioid agonist treatments (OAT). While these treatments are successful for many individuals, they have a variety of limitations. It is critical to trial alternative treatments if conventional opioid agonist treatment options are not successful for a proportion of patients who use illicit fentanyl. Main body Prescription fentanyl has been widely used for pain management. The use of transdermal fentanyl, specifically, which provides long acting and stable drug levels post-titration over several days, should be explored as an opioid agonist treatment option. The use of transdermal fentanyl for patients who use illicit fentanyl is currently being piloted in Vancouver, Canada. To address potential diversion, the patch is signed, dated, and a film dressing is applied to mitigate tampering. Evaluation outcomes are still pending, but there have been no adverse outcomes thus far and clinical improvements have been noted for many patients. This exploratory therapeutic approach should be considered across multiple settings and rigorously evaluated. Conclusions There are known limitations to existing OAT options and there is a need to urgently evaluate alternative strategies for patients who are using illicit fentanyl not successfully treated with conventional OAT. Many patients may be attracted to, and retained in, fentanyl assisted treatment. This may be another strategy for certain patients to prevent harms caused by illicit fentanyl use, including overdose and death.